PELATIHAN QUALITY COST PADA UMKM UNTUK MENGHADAPI PERSAINGAN PRODUK - Rasyid, Ardiansyah; Jayanti, Yunia Arinda; Bravo, Christiandinata Tjandra (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
The purpose of the activity is to help business owners have a stock of knowledge about quality costs, so that business owners can increase product excellence compared to other competitors in the market. The partner chosen in the PKM activity is a homemade handicraft business with the Damar Handy Craft brand, various kinds of raw materials are combined and processed into handicraft products such as decorative lamps, decorations and so on. Damar Handy MSMEs are domiciled in the city of Serang, Banten Province. Based on initial observations to partners communicated directly with business owners, the main problem of partners lies in the absence of understanding of the classification of quality costs and their application. This is due to the partners' lack of knowledge about quality costs so that the handicraft products that are successfully made do not have adequate quality with an efficient level of cost expenditure. The method offered in the activity is training/socialization on quality costs and the classification and utilization of quality costs in online handicraft processing. The results of the activity show that the implementation of the training went smoothly, there was a discussion between the partners and the PKM team. It is hoped that knowledge about quality costs can be able to overcome partner problems, so that partners can increase product excellence compared to competitors.